Long-term efficiency of cataract surgery with hydrophilic acrylic Ioflex intraocular lens (Clinics, 2017)
OBJECTIVE: To evaluate the efficiency of long-term cataract surgery using low-cost intraocular lens implantation in community campaigns. METHODS: Fifty-eight randomly selected patients were evaluated four years after phacoemulsification and Ioflex intraocular lens implantation. Causes of low visual acuity related to the intraocular lens were evaluated, and treatment costs were calculated. RESULTS: The mean age of patients was 72±10.2 years. Four years after surgery, 25 eyes (43.0%) had decreased visual acuity related to the intraocular lens: posterior capsule opacification was noted in 24 eyes (41.3%), and intraocular lens opacification was noted in one eye (1.7%). The total cost of the post-surgical complication treatments represented 6.3% of the initial budget of the entire surgical patient group. CONCLUSIONS: The efficiency of cataract surgery with low-cost Ioflex intraocular lens implantation was significantly reduced in a long-term follow-up study because postoperative complications related to intraocular lenses emerged at higher rates than when the gold-standard treatment was used.